ENFORCING THE LECTURER PERFORMANCE IN ASEAN ECONOMIC COMMUNITY ERA - Tuegeh, Oktavia D. M. (Journal of Asean Studies on Maritime Issues, 2016)
ASEAN Economic Community era enhance the development in every single sector in management practice. In education, lecturer are forced to develop their performance to address this challenge. To develop their performance need clear motivation and high satisfaction. The relationship between job satisfaction and motivation have influence on lecturer performance in Manado State University Tondano. This study aim to explain the simultaneous effect of job satisfaction and work motivation on lecturer performance at Manado State University Tondano. The population in this study were all lecturers at Manado State University Tondano totaling 120 respondents, consisting of 76 men and 44 women. By using a purposive sampling method the sample is 80 respondents. Using multiple regression as a data analysis tool, this study found that job satisfaction and motivation have a significant effect on the performance of lecturers at Manado State University Tondano.